Zoom in: Exploring perceptions of the multiplication symbol (×) up close - Ardiansari, Lia; Rozi, Mohammad Sahrul; Herdiyanti, Shellyna (Mahesa Research Center, 2024)
This study explored the perceptions of 51 prospective elementary school teachers selected using purposive sampling technique regarding the multiplication symbol (×) in arithmetic operations. Using a qualitative hermeneutic phenomenological approach, data were collected through task-based interviews administered to education students specializing in elementary education. The tasks were designed to explore candidates’ understanding and interpretation of the ‘×’ symbol, including uncovering conceptual images, understanding the ‘×’ symbol in different contexts, ability to represent the ‘×’ symbol, flexibility in relating the ‘×’ symbol among concepts, and problem-solving skills. Data analysis involved thematic coding and interpretive analysis to uncover patterns and insights into candidates’ cognitive frameworks. The findings revealed significant variation in candidates’ understanding of the ‘×’ symbol, influenced by their educational background and personal experiences with mathematics. This study highlights the need for improved mathematics instruction and curriculum design to equip future teachers with a deep and accurate understanding of arithmetic symbols, which is critical for effective mathematics teaching at the elementary level.